JATUH TEGANGAN PADA TRANSFORMATOR DISTRIBUSI 2.000 KVA TEGANGAN 20.000 / 400 VOLT DI PT. ASTRA HONDA MOTOR - , WENNY INDRIANI; , Ir. Daroto, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Drop voltage is one of the reasons for the declining quality of electric power. At number 5 transformer PT. XYZ Plant 1 and its loads found substantial drop voltage, which may cause damage to the engines of production. Therefore to determine whether the large drop voltage and power quality is still good or not, analyzed the drop voltage across the transformer and the cables. Analysis on the transformer itself is done by calculating the parameters of transformer, such as Req and Xeq through measurement and some parameters assumed by nameplate and characteristics of the transformer. While analysis of the cables is done by considering the distance and the type of cables used. From the analysis found that the voltage drop that occurs in transformer and cables used are within the standards set by PT. PLN (Persero) is Â± 10% so as not to cause damage to the loads such as 3 phase electric motors. Result of writing this final project is to analyze how much voltage drop that occurs in the transformer and conductor as well as its influence on the load.